Home to 1st base = 90 ft
1st base to 2nd base = 90 ft
2nd base to 3rd base = 90 ft
3rd base to home = 90 ft
so we have a total of : (90 * 4) = 360 ft
there are 3 ft in 1 yd....
so in 360 ft, there are : 360/3 = 120 yds <==
or u could just figure it between each base....90 ft = (90/3) = 30 yds per base...and u have 4 bases....so that (4 * 30) = 120 yds
Answer: 1
Step-by-step explanation:
8/-4 ÷ -3/9
8/-4 × 9/ -3 = 6
Answer:
b. 4x^2 -7x +5
Step-by-step explanation:
When you know a sum and one of its contributors, you can find the other by subtraction. The other trinomial is ...
(7x^2 -5x +4) - (3x^2 +2x -1)
= (7 -3)x^2 +(-5 -2)x +(4 -(-1))
= 4x^2 -7x +5 . . . . . matches B
Answer:
Step-by-step explanation:
Hope this helps!
=)